Description of a new species of the genus Leporinus Spix (Characiformes: Anostomidae) from the rio Araguaia, Brazil, with comments on the taxonomy and distribution of L. parae and L. lacustris - Britski,Heraldo A. (2008)
A new species of the genus Leporinus is described from the rio Araguaia, in Mato Grosso and Goiás states, Brazil. The new species has the dental formula 4/3, a unique feature within the genus; all other species of Leporinus have dental formulae 3/3, 3/4 or 4/4. In addition, the new species can also be distinguished by the following combination of characters: 36 to 37 scales in the lateral line, 4/4.5 or 4/5 series of scales in the transversal line, 16 circumpeduncular scale series, anal fin surpassing base of lower caudal-fin rays and three blotches along the lateral line. The new species shares with L. parae and L. lacustris a rather deep body, terminal mouth, long anal fin, three small dark blotches on the lateral line, the latter two, particularly the last one, usually fading, and preference for lentic habitats. Comments on the taxonomy and distribution of the species L. parae and L. lacustris are provided.